ANALISIS SENTIMEN MAHASISWA TERHADAP LAYANAN BIMBINGAN TUGAS AKHIR - Andi, Andi WIjaya; Rohman Mujahidin; Sasmito (Jurnal Rekayasa Sistem Informasi dan Teknologi, 2023)
Abstract. This study aims to analyze student sentiment towards final assignment guidance services at Nurul Jadid University (UNUJA) using the sentiment analysis method with the Naive Bayes algorithm. Final assignment guidance services play a crucial role in shaping the quality of qualified and competitive human resources in the university environment. However, the assessment of student sentiment towards these services is often complex and can differ from the view of the supervisor. The research approach used is quantitative analysis by collecting student response data through questionnaires and interviews. Student response text data is then processed to clean and format the data before being implemented with the Naive Bayes algorithm. This algorithm will classify sentiment into positive, negative, or neutral sentiment groups based on the information contained in the response text. The results of the sentiment analysis will provide a comprehensive picture of student sentiment towards final assignment guidance services at UNUJA. Recommendations can be generated to improve the quality of academic services, based on the findings and interpretation of the sentiment analysis results